Pengaruh Kepemimpinan Transformasional Dan Komunikasi Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Pegawai Dinas Ketenagakerjaan Kota Makassar - Idrus, Tasmin; Ridjal, Syamsul; Djaharuddin, Dharmawaty (AkMen JURNAL ILMIAH, 2024)
This type of research is descriptive research with a quantitative approach. The sample in this research was 54 people or the total number of State Civil Apparatus within the Makassar City Manpower Office. The data analysis method used is descriptive statistical analysis and path analysis. The research results indicate that both leadership and communication have a significant positive effect on employee performance. Additionally, job satisfaction is shown to mediate the relationship between leadership and employee performance, although it does not mediate the relationship between communication and performance. This research provides important insights into the significance of good leadership and effective communication in enhancing employee performance.